Quality control data of physiological and immunological biomarkers measured in serum and plasma. (November 2015) - Jansen, Eugène; Beekhof, Piet; Cremers, Johannes; Weinberger, Birgit; Fiegl, Simone; Toussaint, Olivier; Bernhard, Jürgen; Gonos, Efstathios; Capri, Miriam; Franceschi, Claudio; Sikora, Ewa; Moreno-Villanueva, María; et al.
Highlights: In the MARK-AGE project 37 physiological and immunological biomarkers were measured in 3637 serum and plasma samples. The quality of the samples was very good as determined by serum/plasma indices. Only 0.24% of all measurements have to be excluded. The quality control of the biomarker measurements showed a mean inter-assay variation of only 4%. Abstract: In two work packages of the MARK-AGE project, 37 immunological and physiological biomarkers were measured in 3637 serum, plasma or blood samples in five batches during a period of 4 years. The quality of the serum and plasma samples was very good as judged by the low number of biomarker measurements (only 0.2%) that were rejected because of a high hemolysis, icteria or lipemia of the samples. Using quality control samples, day-to-day and batch variations were determined. The mean inter-assay variation of the five batches were all below 8%, with an average inter-assay coefficient of variation of all biomarkers of 4.0%. Also the precision of the measurements was very good, because all measurements were between 90% and 115% of the defined target values. A possible mix-up of samples was determined by comparison of the extreme testosterone levels of men and women. It was concluded that 3% of the sample identification could be mixed-up. Considering the complex procedure from collection to analysis, including preparation, handling, shipment and storage, of the samples in the MARK-AGE project, both the quality of the samples and the quality of the measurements are very good.